In Silico Study: Comparison of Binding Affinity of Quercetin and Tak-285 Against HER2 Malignancy Protein - I Putu Widja Putra; Putri, Candra Rini Hasanah; Harman Agusaputra (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2026)
Background : Cancer is a leading global health challenge, driven by various proteins that promote malignant cell growth—one of which is HER2, a transmembrane receptor tyrosine kinase in the ErbB family. TAK-285 is a known HER2 inhibitor. Recently, natural compounds like quercetin have gained attention for their ability to suppress HER2 overexpression and offer therapeutic potential. Objective: This study is to compare the binding affinity between quercetin and the reference inhibitor TAK-285 with the HER2 protein, as well as to analyze the molecular interaction patterns of HER2 using In Silico study. Through this, the study seeks the determine the potential similarity in the inhibition mechanisms of HER2 quercetin and TAK-285. Methods: Experimental study using In Silico docking methods, was performed using AutoDock Vina via PyRx 0.8 to evaluate involving docking interactions between quercetin and HER2, as well as TAK-285 and HER2. Results : The results showed that quercetin binds to HER2 with a binding energy of -8.3 kcal/mol, while TAK-285 shows a stronger affinity with -9.0 kcal/mol. Despite having a slightly lower binding affinity, quercetin successfully interacts with key residues in the HER2 binding pocket and demonstrates potential as a natural HER2 inhibitor.Conclusion: These findings suggest that quercetin may serve as a promising lead compound for HER2-targeted therapy and support further investigation through in vitro and in vivo studies.